Character Education in the Covid-19 Pandemic - Rachmawati Rachmawati (Peneliti.net, 2020)
This study aims to determine the importance of character education for Indonesian students during the Covid-19 pandemic, especially those currently undergoing the online learning process. Character education is so important not only on campus, but at home and in the environment. Furthermore, students in higher education are no longer supervised by their parents during the learning process so that character or manners while studying are no longer things that must be considered and are considered important in distance learning. This research is a literature study sourced from library materials using a qualitative approach. The situation becomes different when classroom learning turns into distance learning and students cannot be fully monitored by lecturers and lack of participation from parents who pay less attention to character education at home.